Clinical oncology and error reduction - Surbone, Antonella; Rowe, Michael, 1947- (Chichester, West Sussex ; Hoboken, NJ : Wiley-Blackwell, 2015)
Clinical Oncology and Error Reduction is the first single-source reference to address the vital topics of recognizing, preventing, and responding to medical errors in clinical oncology.-Filled with practical information for immediate clinical application -Covers topics such as patient safety, error prevention, quality improvement, errors disclosure and apology, and the impact of errors on patients and doctors -Each chapter contains special 'take home' points that highlight issues of particular clinical relevance and application -Prepared by an expert, multidisciplinary, international team of physicians, nurses, researchers, hospital administrators, bioethicists, patients and patient advocates.
Introduction to oncology and medical errors / Antonella Surbone and Michael Rowe -- Recognizing and facing medical errors : the perspective of a physician who is also patient / Itzhak Brook -- Psychological and existential consequences of medical error for oncology professionals / Mary J. Chalino, Evelyn Y.T. Wong, Bradley l. Collins, and Richard T. Penson -- To sue or not to sue : restoring trust in patient-doctor-family relationships / Michael Rowe and Antonella Surbone -- Prevention of errors and patient safety : oncology nurses' perspectives / Martha Polovich -- Prevention of errors and patient safety from the oncologists perspective / Meghan E.S. Shea, Nie Bohlen, and Inga T. Lennes -- Disclosing harmful medical errors / Walter Baile and Daniel Epner -- Do cross-cultural differences influence the occurrence and disclosure of medical errors in oncology / Lidia Schapira, Joseph R. Betancourt, and Alexander R. Green -- Prevention of errors and patient safety : institutional perspectives / Eric Manheimer -- Professional and ethical responsibilities in adverse events and medical errors : discussions when things go wrong / P.M. Forde and Albert W. Wu -- Medical error and patient advocacy / Juanne N. Clarke -- Conclusion : the "given" and "therefores" of clinical oncology and medical errors / Antonella Surbone and Michael Rowe.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Cancer -- Patients; Oncology; Medical errors -- Prevention; Patient advocacy; Medical Errors -- prevention & control; Medical Oncology; Patient Advocacy; Patient Safety; Physician's Role; Medical; HEALTH & FITNESS -- Diseases -- Cancer; MEDICAL -- Oncology; Cancer -- Patients; Medical errors -- Prevention; Oncology; Patient advocacy; Electronic books; Electronic books